PENERAPAN MODEL PROBLEM BASED LEARNING UNTUK MENINGKATKAN KEAKTIFAN DAN HASIL BELAJAR TEKNOLOGI DASAR OTOMOTIF - Viki Vauzi; suparmin suparmin; nurcholish arifin handoyono (Program Studi Pendidikan Vokasional Teknik Mesin, Universitas Sarjanawiyata Tamansiswa, 2020)
The research aims to improve the activeness and learning outcomes of Automatic Basic Technology students of class X SMK Diponegoro Depok Sleman by applying the Problem Based Learning (PBL) learning model. This type of research is Classroom Action Research consisting of three cycles, each of which consists of 4 stages, namely (1) planning, (2) action, (3) observation, and (4) reflection. The subjects of the study were the students of class X SMK Diponegoro Depok Sleman with a total of 23 students. Data collection techniques used were observation, documentation, and quantitative descriptive techniques. The results showed an increase in the activity and learning outcomes of TDO students. In the first cycle, the percentage of students' activeness percentage was 57.398% to 79.41% in the second cycle and increased to 85.21% in the third cycle. While the TDO learning outcomes of students, the average value in the first cycle 61.74 to 72.17 in the second cycle and increased to 79.95 in the third cycle.